Analisis Faktor-Faktor yang Mempengaruhi Pembiayaan Murabahah pada Bank Syariah di Indonesia Periode 2012.05-2015.04 - Utami, Tribudi, Dr. Didit Purnomo, MSi, Muhammad Muhtarom, SH. MH (2016)
Murabaha financing is the most dominant in Islamic banking than other financial products. The Islamic banks more careful in distributing of finance to business world and better finance that has a low risk such a murabaha finance which has required rate of profit that is definitely appropriate with the applied terms. The purpose of this research is to analyze what the variables of Third Party Funds (TPF), Financing to Deposit Ratio (FDR), Inflation and Non Performing Financing (NPF) influence the murabaha financing at Syariah bank in Indonesia with research object is Islamic Commercial Bank and Islamic Business Unit of a Conventional Bank in Indonesia with the secondary data be based on time series monthly period 2012.05- 2015.04. The analysis technique uses the Partial Adjusment Model (PAM) significant (α) at 0,05. The result of t test show that partially TPF and FDR that influence positively and significant the murabaha financing at Syariah bank, NPF that influence negatively and significant the murabaha financing at Syariah bank, and Infation that unfluence negatively and doesn't significant the murabaha financing at Syariah bank in Indonesia. As the result of F test simultaneous show that TPF, FDR, Inflation and NPF simultaneous that influence significant the murabaha financing at Syariah bank in Indonesia in period 2012.05-2015.04.